Relationships between vancomycin minimum inhibitory concentration, dosing strategies, and outcomes in methicillin-resistant Staphylococcus aureus bacteremia - Clemens, Evan C.; Chan, Jeannie D.; Lynch, John B.; Dellit, Timothy H. (Diagnostic microbiology and infectious disease, 2011)
Retrospective study aimed to examine outcomes of methicillin-resistant Staphylococcus aureus (MRSA) bacteremia in relationship to vancomycin minimum inhibitory concentration (VAN MIC) and serum trough concentrations among subjects who had ≥1 blood culture positive for MRSA between April 2008 and August 2009. Treatment failure occurred in 7/24 (29%) subjects with VAN MIC = 2 mg/L versus 20/94 (21%) subjects with VAN MIC ≤1.5 mg/L (adjusted OR 1.11, 95% confidence interval [CI] 0.24–5.14). Among subjects who had documented VAN serum trough concentrations, treatment failure occurred in 5/26 (19%) subjects with concentrations <15 mg/L versus 18/68 (27%) subjects with concentrations ≥15 mg/L (adjusted OR 0.91, 95% CI 0.21–3.84). In conclusion, treatment outcomes were similar regardless of VAN MIC, although there was a non–statistically significant trend towards decreased clinical efficacy among patients with VAN MIC = 2 mg/L. Optimization of VAN pharmacokinetic indices did not appear to correlate with clinical responses.